A Simple Soil Penetrometer for Biological Work - Choudhuri, J. C. Basu (Indian Forester, 1961)
A simple device for measuring compaction of top-soil is described. The method of operation along with field and laboratory data is stated. Possible application of the same in animal and plant ecology has been suggested.